2015
DOI: 10.1002/jmri.24924
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐guided percutaneous transpedicular biopsy of thoracic and lumbar spine using a 0.23t scanner with optical instrument tracking

Abstract: MRI-guided percutaneous transpedicular biopsy is a safe and accurate diagnostic technique to evaluate thoracic and lumbar spine lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Interventional magnetic resonance imaging (IMRI) applications have rapidly developed in recent years. MRI‐guided percutaneous biopsy has been successfully applied to various anatomical regions, such as brain, lung, breast, liver, neck, prostate, and spine. In 2005, 0.23T open configuration C‐arm‐shaped MRI‐guided abdominal biopsy was performed on 31 patients by Kariniemi et al; three pancreatic adenocarcinoma cases were reported and no immediate or late complications occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional magnetic resonance imaging (IMRI) applications have rapidly developed in recent years. MRI‐guided percutaneous biopsy has been successfully applied to various anatomical regions, such as brain, lung, breast, liver, neck, prostate, and spine. In 2005, 0.23T open configuration C‐arm‐shaped MRI‐guided abdominal biopsy was performed on 31 patients by Kariniemi et al; three pancreatic adenocarcinoma cases were reported and no immediate or late complications occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Although MRI guidance is seldom used for CPN, MR scanners have advantages to facilitate interventional procedures. MRI provides good visualization of the retroperitoneal anatomic structures, with no need for contrast media, multiplanar capability, near real‐time imaging, and involves no ionizing radiation, which allow accurate targeting and safe access to avoid penetration into the spinal cord, kidney, liver, major blood vessels, and other critical organs . Most open MRs have sufficient space to allow access and needle adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…A 0.23T open‐configuration MRI system equipped with an Ipath200 optical tracking system (Proview; Philips Medical Systems, Amsterdam, Netherlands) was used to guide and monitor the CPN procedures . A flexible transmit‐receive‐type surface coil of 30 cm diameter was applied to acquire the signal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-clinical studies in canines employed fluoroscopic guidance to percutaneously transplant stem cells into the spinal cord[25,26]. Recently, MRI guidance was used to deliver stem cells to the porcine intervertebral disc[27] and guide transpedicular biopsy in patients[28]. However, these previous studies have not introduced a cannula into the spinal cord through the interlaminar space under MRI guidance, and have not delivered cells to specific locations identified with MRI.…”
Section: Introductionmentioning
confidence: 99%